Health risk assessment for consuming rice, bread, and vegetables in Hoveyzeh city - Abdolkazem Neisi; Majid Farhadi; Kambiz Ahmadi Angali; Arefeh Sepahvand (Toxicology Reports, 2024)
Introduction: People are continuously exposed to contamination, which mainly consists of heavy metals (HMs) and organic compounds. Several metals can get into grains, veggies, and bread through various methods. We estimated the health risk of HM exposure from the consumption of bread, veggies, and rice, considering the per capita amounts of these foods in the Iranian food basket, especially in Hoveyzeh and Azadegan Plain. Material and method: The food products analyzed for the assessment of HMs include different veggies, rice, and bread. The health risk assessment was done with the Hazard Quotient and cancer risk formulae. The buying of vegetables, rice, and bread was done in random order during the fall and wintertime seasons. Result: Tarom rice has the maximum reported levels of Cd (0.55 mg/kg), but Pakistani rice has the lowest level (0.18 mg/kg). Radish shows the highest concentrations of As, Pb, Cr, and Ni among vegetation, while Cress shows the lowest level. The study findings showed that Lavash bread had the highest levels of As (1.31 mg/kg), Cd (0.2 mg/kg), and Ni (1.2 mg/kg), whereas it indicated the lowest level of Cr (0.056 mg/kg). While the non-carcinogenic risk of HMs was evaluated between two groups of adults and children, both groups' HI and HQ levels were less than 1. The maximum HQ and HI scores for children were associated with Arsenic (As), specifically 0.0127 and 0.0137 for Tarom rice, respectively. Nevertheless, the highest HQ and HI scores for adults were associated with As, namely 0.0059 and 0.0064 for Tarom rice, respectively. Conclusion: The evaluation of the carcinogenic risk caused by HM exposure in kids and adults showed that both groups' accumulated lifetime CRs and ILCRs were lower than 1*10–6. Hence, the consumption of veggies, rice, and bread within the study's area does not show an association with the occurrence of chronic diseases resulting from hazardous HMs.